Pendekatan Kognitif dan Afektif dalam Pendidikan Olahraga: Membentuk Karakter dan Keterampilan Sosial Melalui Olahraga - Hasmyati (Jurnal Muara Olahraga, 2025)
This study aims to critically examine the implementation of cognitive and affective approaches in physical education and their implications for developing students’ character and social skills. A descriptive qualitative approach using a literature-based research method was employed to analyze theories, empirical findings, and pedagogical models focusing on the integration of cognitive and affective domains in physical education. Data were obtained through a systematic review of scientific articles published between 2010 and 2025 from databases such as Google Scholar, ScienceDirect, Taylor & Francis, and SpringerLink. The results indicate that instructional models such as Teaching Games for Understanding (TGfU) and Teaching Personal and Social Responsibility (TPSR) effectively enhance strategic thinking, self-reflection, social empathy, and moral awareness among students. Moreover, the physical literacy framework successfully integrates physical, cognitive, and affective domains into a holistic learning experience. Therefore, the integration of cognitive and affective approaches in physical education plays a vital role in fostering character formation, social responsibility, and psychological well-being among learners.